2010
DOI: 10.1111/j.1365-2109.2010.02731.x
|View full text |Cite
|
Sign up to set email alerts
|

A physiological and biochemical approach to selecting the ideal diet for Ostrea edulis (L.) broodstock conditioning (part A)

Abstract: To select the best microalgae for Ostrea edulis conditioning, four single species diets were fed to batches of broodstock, which were then compared using physiological and biochemical approaches. Ingestion and absorption were first studied, showing that Chaetoceros gracilis and Skeletonema marinoï were efficiently ingested (4.9–5.3 mg g−1 h−1) and absorbed (1.9–2.5 mg g−1 h−1) while Tetraselmis suecica led to the lowest physiological responses (0.36 and 0.12 mg g−1 h−1 respectively). When O. edulis were fed an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
3
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 50 publications
0
47
3
1
Order By: Relevance
“…The results of the present study differ in that the fatty acid profiles of main tissues did not show a clear correlation with the diets as it has been shown in our previous work with four other microalgae ( Fig. 3; González-Araya et al, 2010). These results were unexpected, because fatty acid composition in microalgae is generally specific.…”
Section: Fatty Acidcontrasting
confidence: 80%
See 4 more Smart Citations
“…The results of the present study differ in that the fatty acid profiles of main tissues did not show a clear correlation with the diets as it has been shown in our previous work with four other microalgae ( Fig. 3; González-Araya et al, 2010). These results were unexpected, because fatty acid composition in microalgae is generally specific.…”
Section: Fatty Acidcontrasting
confidence: 80%
“…(51%). Although the oysters fed R. salina showed the best ingestion and absorption of the study, the values remained lower than those previously reported with C. gracilis and S. marinoï (≈ 5 mg g −1 h −1 : González-Araya et al, 2010). Absorption efficiency (ae%) ranged from 33 to 51%, while those obtained with the four other microalgae tested in our sister study ranged from 19 to 46% (González-Araya et al, 2010).…”
Section: Fatty Acidcontrasting
confidence: 77%
See 3 more Smart Citations